MIMO wireless networks channels, techniques and standards for multi-antenna, multi-user and multi-cell systems - Clerckx, Bruno (Academic Press, 2013)
Combines a mathematical analysis with a physical and intuitive approach to space-time signal processing, this book derives designs for space-time coding and precoding as well as multi-user and multi-cell techniques, taking into consideration that MIMO channels are often far from ideal.